Regulation of deposit-taking institutions: Price effect at disclosures of new regulations - Ahmad, Nor Hayati; Ariff, Mohamed (Universiti Utara Malaysia, 2005)
This paper presents findings on the impact of revisions to a unique bank regulation yet studied. An old hypothesis in banking literature is tested by examining share price reactions to two-way changes to statutory reserve ratio (SRR) requirement over a recent eight-year period. Announcements of these regulatory changes appear to lead to statistically and economically significant abnormal returns.These new findings suggest that a decrease in statutory reserve has a risk-reducing effect on financial institutions. Thus, his study provides a test of the prediction of theory that SRR is a powerful macroeconomic policy tool to revive an economy in the aftermath of a financial crisis.